“JARGON USED ON TIKTOK CHECK…”: LANGUAGE VARIATION REVISITED - Vita Lutfiah; Emy Sudarwati (LLDIKTI Wilayah X, 2021)
This research focuses on two aspects of the jargon used in the TikTok app: form and context. The aim of this study is to define jargon and determine its type and specific significance. A qualitative descriptive approach is used to discover these aspects. The data collection technique used was data collection on the TikTok application. The data analysis process involves evaluating all data collected from the TikTok application's data collection results and analyzing it using a systematic procedure that includes identifying jargon and explaining its context. The data discovered during the research have been included in this journal as part of a descriptive qualitative study. According to the findings of the study, TikTokers' jargon consists of FYP, edition, check, damage, valid no debat, bund, jamet, gelay, kentang, ngotak, virtual date, tingting, canda ya canda. The advantage of this research in teaching and learning English is that it can be used as a resource for those who want to expand their knowledge of jargon, especially potential researchers interested in conducting research on similar topics. It can also be used as a way to help students or anyone improve their communication skills in English, especially when using jargon.